Controlled aggregation in conjugated polymer nanoparticles via organic acid treatments - Ko, Yoon-Joo (2011)
Understanding and controlling aggregation structures of conjugated polymers (CPs) in aqueous solutions is critical to improving the physical and photophysical properties of CPs for biological applications. Here, we present spectroscopic evidence, including nuclear magnetic resonance (NMR) spectroscopic results, that different organic acid treatment induces different aggregation structures and photophysical properties of CPs in water. Conjugated polymer nanoparticles (CPNs) were fabricated by treating a non-aqueous soluble, primary amine-containing poly(phenylene ethynylene) (PPE-NH(2)) with organic acids followed by dialysis. CPNs formed by acetic acid (AA) treatment (CPN-AAs) exhibit characteristics of loose aggregation with minimal π-π stacking, while CPNs formed by tartaric acid (TA) treatment (CPN-TAs) exhibit a high degree of π-π stacking among PPE-NH(2) chains. The controlled aggregation for a specific application was demonstrated by comparing the fluorescence quenching abilities of the CPN-AAs and the CPN-TAs. A doubled Stern-Volmer constant was obtained from the densely packed CPN-TAs compared to that of the loosely aggregated CPN-AAs.